Comparisons of liver transplant from DCD outcomes in high-utilization centers versus low-utilization centers in the US: a systematic review and meta-analysis - Manzi, Joao Lucas Lima; Oliveira, Eduarda Saba; Rombach, Sarah; Turra, Vitor; Zaragoza, Simone; Bababekov, Yanik; Nydam, Trevor; Tector, Alfred Joseph; Vianna, Rodrigo; Abreu, Phillipe (Frontiers in Immunology, 2025)
Purpose/ObjectiveDonation after Cardiac Death (DCD) grafts are considered to be inferiors compared to Donation after Brain Death (DBD) grafts. Consequently, many transplant centers employ highly selective criteria for utilizing DCD, while others use them more liberally, potentially gaining greater expertise with this procedure. This disparity in approach raises questions about the impact of organ selection versus the benefits of increased experience with DCD organs. We performed a systematic review and meta-analysis to evaluate various outcomes in centers with high and low utilization rates of DCD.Materials/MethodsElectronic databases PubMed, Embase, and Cochrane Library were systematically searched up to May 24th, 2023, for studies related to liver transplantation (LT). This search was conducted in accordance with PRISMA guidelines. The inclusion criteria focused on studies involving controlled DCD published within the last five years, and reporting on at least one of the outcomes of interest. Data was extracted and analyzed using a random-effects generalized linear mixed model with a 95% confidence interval (CI). The primary outcomes assessed were patient survival and graft survival. Heterogeneity among the included studies was evaluated using the I2 test, with I2>40% considered significant, and further explored through influence analysis. Subgroup meta-analysis by DCD utilization rate was done for each outcome. An analysis of the Organ Procurement & Transplantation Network (OPTN) database was performed on October 30th to determine the DCD rates and percentiles.ResultsSeven studies encompassing 898 patients were analyzed. In parallel, data from 151 centers were examined using the OPTN database, determining the rates of DCD utilization in each center over the past five years. Centers from the seven studies were divided into five high-utilization centers (HUC) and two low-utilization centers (LUC), with the 80th percentile (13.33% DCDs/Total LT) used as the threshold for high-utilization. Overall, the 1-year patient survival rate was 94.5% (95%CI: 92.4-96.1; I2 = 0%). HUCs had a rate of 94.6% (95%CI: 92.4-96.1; I2 = 0%), and LUCs had 93.7% (95%CI: 79.1-99.2; I2 = 0%), with a p=0.84. The overall 1-year graft survival rate was 90.6% (95% CI: 88.4-92.4; I2 = 0%). HUCs showed a 1-year graft survival of 90.9% (95%CI: 88.4-92.9; I2 = 0%), and LUCs showed 89.4% (95%CI: 83.8-93.2; I2 = 0%), p=0.54. The overall incidence of ischemic cholangiopathy was 10.3% (95% CI:7.9-13.3; I2 = 0%). The total rate of primary nonfunction was 1.5% (95% CI: 0.7-3.1%; I2 = 46%).ConclusionOur findings indicate no statistical difference in outcomes between high and low-utilization centers for DCD liver transplants, possibly suggesting that the higher selection in low-utilization centers is compensated by a greater experience in high-utilization centers.